Development Strategy For Kopi Gunung Kelir Agrotourism, Semarang Regency, Indonesia - Mubarokah; Mirza Andrian Syah; Sri Widayanti; Mukhlis (Postgraduate, University of Mataram, 2024)
The Rahayu IV Farmer Group aims to capitalize on this potential by developing Kopi Gunung Kelir Agrotourism. However, visitor activity has been low, likely due to the site's limited visibility, its newness, and its remote location. This lack of awareness and accessibility affects its growth as a tourist destination. This study aims to determine the current conditions and determine the strategy plan for the development of Kopi Gunung Kelir Agrotourism through Business Model Canvas and SWOT analysis. The BMC assessed nine key business components and aims to facilitate the preparation of strategic plans through each component or block in the business model, while SWOT analysis identified internal strengths and weaknesses, and external opportunities and threats. Key strengths included educational tourism offerings, high-quality Robusta coffee production, and scenic landscapes. Weaknesses were limited infrastructure, promotion, and accessibility. Opportunities arose from the growing eco-tourism and coffee culture, while threats included competition from other agrotourism sites and fluctuating visitor interest. The study proposed strategies like expanding road access, optimizing digital marketing through platforms like TikTok, improving visitor facilities, and fostering partnerships with sponsors and local stakeholders.